Peningkatan Hasil Belajar Biologi Sel dengan Menggunakan Metode Pembelajaran Game Plants Vs Zombies - Delfa Oktaverina; Meity Tanor; Hasmiati Hasmiati (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Education in Indonesia continues to grow, but the main challenge in learning Biology, especially in cell material, is the lack of student involvement. Many students rely more on memorization methods than understanding concepts, which impacts their low learning outcomes. This study aims to explore the effectiveness of the Plants vs Zombies game-based learning method in improving the cognitive learning outcomes of students in grades XI-B at SMA Negeri 1 Tondano, especially in cell biology materials. This study uses the Classroom Action Research (PTK) approach, which is carried out in two cycles. In the first cycle, students were invited to learn through the Plants vs Zombies game which was integrated with the Team Games Tournament (TGT) learning model. Data is collected through observation and cognitive tests to measure student learning outcomes. The results showed a significant increase in student learning outcomes. The average score of students increased from 71.2 to 87.27, with the highest score reaching 92.3 and the lowest score being 76.9. Students also show improvements in engagement, collaboration, and motivation to learn. This research indicates that the application of games as learning media can make abstract biology material more interesting and easy to understand. In addition, this study also highlights the important role of teachers in facilitating game-based learning. The implications of this study show that game-based methods can be an innovative solution in improving the quality of learning in the 21st century.